Early Experience with Low Contrast Imaging (LCI) Technology during Neuroendovascular Interventional Procedures. Issue 6 (9th April 2014) - Mokin, Maxim; Levy, Elad I.; Snyder, Kenneth V.; Siddiqui, Adnan H.
ABSTRACT BACKGROUND AND PURPOSE Early recognition of complications during intracranial neuroendovascular interventions is important for medical decision making and prompts administration of life‐saving treatments. Low contrast imaging (LCI) provides computed tomographic (CT)‐like images of anatomical brain structures, capable of detecting hydrocephalus and intracranial hemorrhage complications. We present our early experience with LCI using the Toshiba Infinix‐i biplane angiographic suite during neurointerventional cases, including acute stroke interventions, aneurysm embolization, and subarachnoid hemorrhage management. METHODS Six patients underwent LCI during various neuroendovascular procedures. We describe clinical and imaging findings and provide visual comparison of LCI with conventional noncontrast cranial CT imaging. RESULTS Our initial experience shows that LCI is capable of detecting or excluding intracerebral hemorrhage and hydrocephalus during neurointerventional procedures as well as confirming ventriculostomy catheter placement when compared to noncontrast CT imaging. Motion artifact is a major limitation associated with this technology and can be overcome in part by performing shorter duration rotation sequences. CONCLUSIONS LCI is a promising tool in the arsenal of a neuroendovascular interventionist, especially when a complication is suspected during an intervention, potentially obviating the need for immediate transfer of the patient to a conventional CT scanner. Further studies comparing LCI with conventional noncontrast CT imaging are necessary.